Pulmonary hypertension in pregnancy - Bernolian, Nuswil; Kesty, Cindy; Mirani, Putri; Lestari, Peby Maulina; Martadiansyah, Abarham; Agustria, Rizky (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2024)
Pulmonary hypertension (PH) is a persistent increase in mean pulmonary arterial pressure (mPAP) of at least 20–25 mm Hg during right cardiac catheterization. For every million patients, there were 97 PH cases. Women are more likely than men (1.7:1) to receive a diagnosis, with a mean age of 37 years. The classification, pathophysiology, mechanism, and management of postpartum hemorrhage (PH) are the main aims of this review study. Pulmonary artery hypertension (PAH), pulmonary hypertension (PH) associated with left heart disease, pulmonary hypoxia and/or lung illnesses, chronic thromboembolic PH, and PH with unknown multifactorial processes are the five categories into which PH is divided. Women, particularly those of reproductive age, make up about 80% of individuals with idiopathic PAH. Pregnancy-related PH is one of the long-standing heart conditions with a significant morbidity and mortality rate. Its estimated death rate ranges from 30.56%. Pregnancy is therefore not advised in PH patients. Treating people with PH requires early diagnosis and effective treatment. These patients have optimism because of the impending PH medications (phosphodiesterase type 5 inhibitors, nitric oxide, endothelin receptor antagonists, and calcium channel blockers) as well as the advancements in hemodynamic monitoring and intensive care in PH specialty facilities. Pregnant women with PH should be treated with a multidisciplinary approach, such as obstetricians, cardiologists, intensivists, and neonatologists.